The THE EFFECT OF USE OF CROSSWORD PUZZLE LEARNING MEDIA ON CLASS VII STUDENT LEARNING OUTCOMES IN ISLAMIC EDUCATION SUBJECT AT SMPN 4 KLARI KARAWANG: Analysis of the impact of the use of crossword puzzles on improving student learning outcomes in Islamic religious education - Naura, Naurasyifa Iftinannisa; Debibik, Debibik Nabilatul Fauziah; Ulya, Neng Ulya (STAI Nurul Falah Airmolek, 2025)
This study aims to examine the effect of using Crossword Puzzle learning media on student learning outcomes. This study was conducted at SMPN 4 Klari Karawang in class D as an experimental class and class E as a control class, in the subject of Islamic Religious Education. This study used a quantitative approach. The method used in this study is Quasi-Experimental with Nonequivalent Control Group Design. The population taken from this study was 472 students, and the sample taken was 84 students consisting of 43 students in the experimental class and 41 students in the control class. The increase in student learning outcomes can be seen from the increase in the average post-test score of students using Crossword Puzzle media, reaching 62.79, while the control class was only 54.83. To see the effect of using Crossword Puzzle learning media on student learning outcomes, it can be seen from the results of the N-gain test calculation; the N-gain test for the experimental class was 0.3502, which has a moderate category with a percentage of 35%. So, it can be concluded that there is an influence of the use of Crossword Puzzle learning media on student learning outcomes in the Islamic Religious Education subject for class VII D at SMPN 4 Klari Karawang. Keywords: Crossword Puzzle, Learning Outcomes, Islamic Religious Education.